Breeding efforts to mitigate damage by heat stress to spikelet sterility and grain quality - Ishimaru, Tsutomu; Hirabayashi, Hideyuki; Sasaki, Kazuhiro; Ye, Changrong; Kobayashi, Asako (Informa UK Limited, 2016)
Global warming is predicted to aggravate the risk of unstable crop production. It is of great concern that damage to rice spikelet sterility and grain quality will increase, resulting in yield and economic losses. To secure the global food supply and farmers’ income, the development of rice cultivars with heat resilience is a pressing concern. Regarding spikelet sterility, rice cultivars with heat tolerance at different growth stages have been identified in recent years. The early-morning flowering (EMF) trait is effective in heat escape because it shifts the time of day of flowering to earlier in the morning when it is cooler. Although varietal differences are very small, there are some genetic resources for EMF in wild rice accessions. Regarding heat-induced grain chalkiness, heat-tolerant japonica cultivars for mitigating white-back type of chalky grains (WBCG) were found. Quantitative trait loci for heat tolerance at flowering, EMF, and for WBCG in grain quality have been mapped on the rice chromosomes. Further genetic efforts have been successfully connected to the development of near-isogenic lines for each trait with tagged molecular markers. These breeding materials are quite unique and useful in facilitating marker-assisted breeding toward the development of heat-resilient rice in terms of spikelet sterility and grain quality